Given:
[tex]f(x)=4xcos^{-1}(2x+4)-\sqrt{3-3x^2}[/tex]
Using
[tex]\frac{d}{dx}cos^{-1}(x)=-\frac{1}{\sqrt{1-x^2}}[/tex]
we derive
[tex]\frac{d}{dx}4xcos^{-1}(2x+4)[/tex]
[tex]=4cos^{-1}(2x+4)-\frac{8x}{\sqrt{1-(2x+4)^2}}[/tex]
Similarly, using
[tex]\frac{d}{dx}\sqrt{x}=\frac{1}{2\sqrt{x}}[/tex]
we derive
[tex]\frac{d}{dx}(-\sqrt{3-3x^2})[/tex]
[tex]=\frac{3x}{\sqrt{3-3x^2}}[/tex]
Therefore, the derivative is
[tex]f'(x)=\frac{d}{dx}(4xcos^{-1}(2x+4)-\sqrt{3-3x^2})[/tex]
[tex]=4cos^{-1}(2x+4)-\frac{8x}{\sqrt{1-(2x+4)^2}}+\frac{3x}{\sqrt{3-3x^2}}[/tex]